Peranan Objek Wisata dalam Peningkatan Kesejahteraan Masyarakat: (Studi Kasus Objek Wisata Pohon Seribu, Sasak Ranah Pasisie) - Dewi Novita Sari; Yossi Eriawati; Fawza Rahmat (Universitas 45 Surabaya, 2024)
This study aims to determine the process of developing the Pohon Seribu tourist attraction, and to determine the economic welfare of the community as business actors around the tourist attraction whether it is affected by the development of the Pohon Seribu tourist attraction in Kejorongan Pondok Sasak Ranah Pasisie District. This research uses qualitative methods by using data collection techniques through interviews, observation, and documentation. Qualitative method is a method that focuses on in-depth observation, therefore, the use of qualitative methods in research can produce a more comprehensive study of a phenomenon. The result of this research is that the development of Pohon Seribu tourist attraction has an impact on the economic welfare of the community around the tourist attraction. In the economic field, there is an increase in the livelihood of the surrounding community, there is a shift in livelihoods. As a result of the tourist attraction, the income received by the community has increased compared to before the tourist attraction. In addition to the economic field such as socio-culture, with the location of tourist attractions making the surrounding community to continue to interact with tourists who visit, this has an impact on improving the welfare of the community is a change in the mindset of the community for the better. Pohon Seribu tourist attraction results in changes in behaviour and better language style.